Preliminary experience in the treatment of hip necrosis with BIOS screws associated with growth factors - Strigini, Giacomo; Ghidoni, Laura; Quattrini, Fabrizio; Bellina, Giorgio; Ciatti, Corrado; Fiazza, Caterina; Maniscalco, Pietro (Acta Biomedica Atenei Parmensis, 2020)
ntroduction: In this paper we present the preliminary results obtained in our clinic with the use of BIOS screws associated with injection of growth factors in the treatment of cephalic necrosis of the femoral head. Materials and methods: In the division of Orthopedics and Traumatology at Guglielmo da Saliceto” hospital in Piacenza were treated between 2012 and 2016 with the proposed technique 8 case of necrosis of the femoral head in 6 patients with a mean age of 41.8 years (between 31 and 60 years). All patients before surgery were affected by debilitating pain with VAS greater than 7 and functional limitation of the range of motion of the hip. In all patients was performed a decompression of the femoral head using cannulated screws BIOS and injection through the implants of growth factors. Results: Our results have been extremely positive. All patients treated at two months have reported the resolution of the pain that affected them before surgery and the recovery of the function of the hip. At the last clinical control carried out no patient experienced recurrence of any symptoms related to necrosis. Discussion: Cephalic necrosis due to various possible etiologies is a not so rare condition, often affecting young patients with high functional demands. Only few years ago the gold standard treatment for this kind of pathological condition was hip prosthesis and this fact was associated with long term complications related with the young age of patients. The treatment presented is simple, fast and very effective in allowing the penetration of growth factors through bony trabeculae of the femoral head, due to the fenestratures inside the screws. The results obtained in our experience are certainly promising, though longer follow-up is needed to evaluate the functional outcome long and to evaluate the possible re-emergence of pain. Conclusion: Conservative treatment using BIOS screws associated with growth factors in femoral head necrosis in our experience combine a low invasiveness to excellent functional results and should therefore be considered a valid option in treating this pathology in young patients.